The change of drug utilization in China’s public healthcare institutions under the “4 + 7” centralized drug procurement policy: Evidence from a natural experiment in China - Lu, Jiancheng; Long, Hongfei; Shen, Yuan; Wang, Jing; Geng, Xin; Yang, Ying; Mao, Zongfu; Li, Jinghua (Frontiers in Pharmacology, 2022)
Background: Improving drug accessibility and rational drug use are major challenges for China’s healthcare reform. In 2018, the Chinese government introduced a novel nationwide policy of centralized drug procurement for off-patent drugs, focusing on improving drug utilization patterns of public medical institutions. Objective: To estimate the impacts of the Chinese centralized drug procurement policy (the so-called “4 + 7” policy) on drug utilization in public medical institutions. Methods: A retrospective natural experimental design and difference-in-difference method were applied using cross-region data extracted from the national procurement database. Eleven “4 + 7” pilot cities (intervention group) and eleven non-pilot provinces (control group) were matched. In addition, “4 + 7” policy-related drugs (n = 116) were selected as study samples, including 25 drugs in the 4 + 7” procurement List (“4 + 7” List drugs) and their alternative drugs (n = 91) that have not yet been covered by centralized procurement policy. Then, the “4 + 7” List drugs were divided into bid-winning and non-winning drugs according to the bidding results, and they were sorted into generic and original drugs. Defined daily dose (DDD) was used to standardize the quantity of drugs used. Results: In the 1-year procurement period, the overall completion rate of agreed procurement volume reached 191.4% in pilot cities. Owing to policy impact, the consumption increased by 405.31% in bid-winning drugs (β = 1.62, p < 0.001) and decreased by 62.28% (β = −0.98, p < 0.001) in non-winning drugs. The overall use proportion of bid-winning drugs increased from 17.03% to 73.61% with statistical significance (β = 1.48, p < 0.001), and increments were also detected in all healthcare settings, regions, and anatomical therapeutic chemical (ATC) categories (all p-values < 0.05). Generics and originators were detected with 67.53% increment (β = 0.52, p < 0.001) and 26.88% drop (β = −0.31, p = 0.006) in consume volume. The use proportion of generics increased from 59.23% to 78.44% with significance (β = 0.24, p < 0.001), as well as in tertiary hospitals (β = 0.31), secondary hospitals (β = 0.23), and primary healthcare centers (β = 0.11) (all p-values < 0.001). The use proportion of relatively quality-guaranteed drugs (i.e. bid-winning and original drugs) increased from 56.69% to 93.61% with significance (β = 0.61, p < 0.001), and similar increments were also detected in all healthcare settings, regions, and ATC categories (all p-values < 0.05). Conclusion: Healthcare providers demonstrated good compliance with the “4 + 7” policy in completing contracted procurement volume. Centralized drug procurement policy promoted drug consumption gradually concentrated on bid-winning drugs, generic drugs, and more importantly, quality-guaranteed drugs.